(untitled) (REMUNOM, 2025)
Public accounting plays a fundamental role in the management of government resources, promoting transparency, control, and legality in public administration. With the enactment of Law No. 14,133/2021, the new legal framework for public procurement and contracts in Brazil, new requirements were imposed on public accounting, requiring technical and structural adaptations by government entities. Public accounting and procurement regulations complement each other by ensuring transparency, efficiency, and legality in the use of public resources. While accounting records and controls the state’s finances, procurement regulates contracts, preventing irregularities and waste. Together, they strengthen integrity, control, and accountability in public administration. This study aims to analyze the impacts of this legislation on public accounting, highlighting the main challenges faced by professionals in the field in the process of adapting to the new regulations. This research is qualitative and exploratory in nature, and was conducted through a bibliographic survey and document analysis. The results show that, although the new law represents significant advances in the modernization of public administration, its implementation depends on investments in training, systems modernization and integration between administrative sectors.